Optimal Sizing and Techno-Economic Evaluation of Microgrids Based on 100% Renewable Energy Powered by Second-Life Battery - Demirci, Alpaslan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
The rapid development of distributed renewable energy has made energy storage essential for demand reliability and flexible energy management. Due to the high investment costs of fresh batteries (FB), achieving a positive and efficient economy takes work. However, second-life batteries (SLB), whose capacity decreases by 20-30% after the first use, can be preferred as alternative energy storage to overcome this challenge. This paper investigates the renewable potential of shared energy storage and the feasibility of FB&SLB for prosumers. In addition, threshold points are determined by examining the financial obligations associated with an increasing share of renewables on the path to 100% renewable energy. Moreover, the impact of carbon taxes on extra CO(2)d reduction costs is assessed depending on the carbon quota. The results confirm the superiority of SLB, which increases throughput by 11.5% while reducing CO2 by 9.4%. Renewable fractions (RFs) above 59.2% and 87% in optimal hybrid power systems (HPS), in different climate potentials, and for low and high energy tariffs lead to costly investments. Increasing the carbon tax could reduce the cost of CO2 reduction by up to 5.2 $/kg in the early stages of carbon limits while avoiding extra costs of up to 2.1 $/kg for FB at lower CO2 limits. In contrast, increasing RF from 95% to 100% would increase net present cost (NPC) by up to 122.65%. It will be more critical than ever for governments to support prosumers' financial trade-offs in the transition to clean energy.
Keywords: Carbon emission; carbon tax; energy storage; renewable energy; second-life battery; LIFE-SPAN; IMPACTS; COST; GENERATION; SUBSIDY; SYSTEMS; LITHIUM; STORAGE; MODEL; WIND; Computer Science; Engineering; Telecommunications